PENERAPAN AZAS KEADILAN PADA PERJANJIAN ASURANSI DALAM UPAYA MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP PEMEGANG POLIS - Santri, Selvi Harvia (UIR Law Review, 2024)
Humans will always face risks that cause losses in carrying out their daily activities, both risks to property and life. The policy serves as written proof that insurance has occurred. In the case of taking out a policy, the position of the insurer will be stronger than that of the policy holder or insured so that injustice occurs, where in practice the policy has been prepared by the insurance company, so this brings benefits to the insurance company itself, the company has the right to determine the contents of the agreement, the party The insured is in a weak position because he does not participate in determining the contents of the agreement, so a form of legal protection is needed for the policy holder or insured (consumer). There is an imbalance between the rights and obligations of the parties. So there is the potential for insurance companies to tend to protect their interests in such a way by setting a number of provisions that limit the rights of the insured so that the standard contract can become a unilateral clause